Effects of Workers’ Remittances on the Home Country: The Case of Bulgaria - Minchev, Vesselin (Research Papers, 2021)
The present report reviews issues, related to the compensation of employees and the remittances of Bulgarian emigrants. Data based on information from international institutions and from the Bulgarian National Bank, regarding the relative shares of these two variables in GDP, is provided. On the basis of information from an empirical sociological study, carried out in 2017 within the project: “Return Migrants: Segmentation and Stratification of Economic Mobility” the profile of individuals supporting their relatives, who remained in the country, is outlined. An answer is sought to the question of what drives the remittance behaviour of the return migrants during their stay abroad.
Keywords: Compensation of employees; Workers’ remittances; Remittance behaviour; For-purpose of remittances; Return migration